1986
DOI: 10.1177/0011000086141005
|View full text |Cite
|
Sign up to set email alerts
|

The Research Training of Counseling Psychologists

Abstract: Participants were 355 randomly selected Division 17 members who responded to a survey concerning their assessment of their own research skills, their research training, and the major influences on their research skill and interest. Respondents reported that graduate programs contribute adequately to their skills in research design, statistics, and writing, but contribute less to their computer skills and practical research skills. Respondents, on average, felt confident about their research skills with the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 9 publications
3
47
0
Order By: Relevance
“…Reports have shown that physicians are more likely to enter research careers if they are exposed to research opportunities during medical school (Segal et al, 1990). Furthermore, research by Royalty and Reising (1986) suggests that ''the research environment may have most of its positive influence on research attitudes within the first few years of training'' (Gelso and Lent, 2000, p. 124). Efforts, such as the NIH Predoctoral Clinical Research Training Awards are aimed at providing early research learning opportunities, but rigorous clinical demands imposed by U.S. accreditation requirements, place a high demand on residents' time and reduce their ability to participate in research activities.…”
Section: Person Interactions With a Complex Environmentmentioning
confidence: 99%
“…Reports have shown that physicians are more likely to enter research careers if they are exposed to research opportunities during medical school (Segal et al, 1990). Furthermore, research by Royalty and Reising (1986) suggests that ''the research environment may have most of its positive influence on research attitudes within the first few years of training'' (Gelso and Lent, 2000, p. 124). Efforts, such as the NIH Predoctoral Clinical Research Training Awards are aimed at providing early research learning opportunities, but rigorous clinical demands imposed by U.S. accreditation requirements, place a high demand on residents' time and reduce their ability to participate in research activities.…”
Section: Person Interactions With a Complex Environmentmentioning
confidence: 99%
“…thereby developing counselors' research skills, which will continue to be useful in their practices (Bishop & Bieschke, 1998;Campbell & Robinson, 1990;Lundervold & Belwood, 2000;Robinson. 1994;Royalty & Reising. 1986).…”
mentioning
confidence: 99%
“…Areas of inquiry have included features of training environments which influence attitudes toward research (Galassi, Brooks, Stoltz, & Trexler, 1986;Gelso, Raphael, Black, Rardin, & Skalkos, 1983;Royalty & Magoon, 1985;Royalty & Reising, 1986;Wampold, 1986), personality characteristics of graduate students that are related to research interests (Betz & Taylor, 1982) and the relationship between training environment influence and personality characteristics in shaping attitudes toward research (Krebs, Smithner, & Hurley, 1991;Mallinckrodt, Gelso, & Royalty, 1990). Research suggests that certain features of training environments, such as the involvement of students in research at early points in their training and an emphasis on philosophy of science (Galassi et al, 1986), as well as the participation in research teams (Gelso et al, 1983) are related to students' positive view of research production.…”
Section: Introductionmentioning
confidence: 99%